Oporność klejów do tapet na działanie grzybów pleśniowych - Piotrowska, M.; Żakowska, Z. (Politechnika Łódzka, 2003)
W pracy zbadano oporność trzech klejów do tapet na działanie grzybów pleśniowych. Wyniki badań wskazują, że wszystkie badanie kleje są oporne na Aspergillus niger, Penicillium expansum, Trichoderma viride, Cladosporium herbarwn i Chaetomium globosum. Aspergillus oryzae i Alternaria alternata jako jedyne źródło węgla wykorzystują kleje. Najsłabszą aktywność grzybobójczą wykazywał klej nr 3. Najbardziej oporna na składniki grzybobójcze wszystkich klejów była Alternaria alternata.

The three wallpaper pastes were tested for resistance to fungal growth. The results indicated that all tested pastes were resistant to growth of Aspergillus niger, Penicillium expansum, Trichoderma viride, Cladosporium herbarum and Chaetomium globosum strains. Aspergillus oryzae and Alternaria alternata were used the pastes as a sole carbon source. The least fungicidal activity was demonstrated wallpaper paste number 3. Alternaria alternata was the ,most resistant to paste fungicidal agents.
Resistance of wallpapers to fungal growth
Keywords: grzyby pleśniowe; klej do tapet - odporność na grzyby pleśniowe; kleje do tapet - właściwości grzybobójcze; mold fungi; wallpaper glue - resistance to mold fungi; wallpaper adhesives - fungicidal properties